Functional anatomy of the equine temporomandibular joint: Collagen fiber texture of the articular surfaces. (November 2016) - Adams, K.; Schulz-Kornas, E.; Arzi, B.; Failing, K.; Vogelsberg, J.; Staszyk, C.
Highlights: The collagen fiber arrangement in the articular surfaces of the equine TMJ is documented using the split-line technique. Central aspects of the articular surfaces feature a uniform rostrocaudal collagen fiber alignment. Peripheral aspects of the articular surfaces feature curved or punctiforme collagen fiber alignments. Specific movements of the TMJ cause different load distributions in different zones of the joint. Abstract: In the last decade, the equine masticatory apparatus has received much attention. Numerous studies have emphasized the importance of the temporomandibular joint (TMJ) in the functional process of mastication. However, ultrastructural and histological data providing a basis for biomechanical and histopathological considerations are not available. The aim of the present study was to analyze the architecture of the collagen fiber apparatus in the articular surfaces of the equine TMJ to reveal typical morphological features indicating biomechanical adaptions. Therefore, the collagen fiber alignment was visualized using the split-line technique in 16 adult warmblood horses without any history of TMJ disorders. Within the central two-thirds of the articular surfaces of the articular tubercle, the articular disc and the mandibular head, split-lines ran in a correspondent rostrocaudal direction. In the lateral and medial aspects of these articular surfaces, the split-line pattern varied, displaying curved arrangements in the articular disc and punctual split-lines in the bony components. Mediolateral orientated split-lines were found in the rostral and caudal border of the articular disc and in the mandibular fossa. The complex movements during the equine chewing cycle are likely assigned to different areas of the TMJ. The split-line pattern of the equine TMJ is indicative of a relative movement of the joint components in a preferential rostrocaudal direction which is consigned to the central aspects of the TMJ. The lateral and medial aspects of the articular surfaces provide split-line patterns that indicate movements particularly around a dorsoventral axis.